Marketing Mix and Quality-Mix Services in Building Satisfaction to Achieve Customer Loyalty - Muzakkar Zul Fuadi; Nurdjanah Hamid; Jusni Ambo Upe (Magister Management, Hasanuddin University, 2021)
One of the businesses growing rapidly and facing the current tight competition is the culinary business. This group of businesses offer the same type of products but vary in prices and services. The purpose of this study was to analyze the linking effect of the marketing mix and service quality on loyalty with the use of customer satisfaction as a mediating variable. Of the 3.834 population calculated at Mokula Coffee Indonesia from October to December 2020, the study collected a sample of 94 customers by observation, interviews, and questionnaires. The data obtained is firstly tested their validity and reliability before applied path analysis. The results indicated that the marketing mix and service quality indicated a positive and significant effect on customer satisfaction. Customer satisfaction, marketing mix, and service quality also have a positive and significant effect on loyalty, indicating great concern for repeat visits and purchases.